Enhancing of coverless image steganography capacity based on image block features - Hadeel Talib Mangi; Suhad A. Ali; Majid Jabbar Jawad (Universitas Ahmad Dahlan, 2023)
The idea of coverless information hiding has seen a great deal of development since it was initially introduced due to its effectiveness in defeating steganalysis tools. However, the capacity for general coverless information hiding methods to conceal information is limited, as well as no previous methods worked at the other requirements such as robustness. In this paper, a coverless image steganography (CIS) method for increasing capacity is proposed while retaining the robustness. The proposed method consists of several steps. Firstly, the secret data is segmented into segments of the length. Secondly, a suitable image that has features similar to the secret message is selected and divided into non-overlapping blocks. Thirdly, these blocks are transformed into the frequency domain by applying discreet wavelet transform (DWT). Fourthly, building a hash sequence table using a suggested hashing algorithm. Fifthly, to reduce search time an indexing table is built based on the generated hash sequence. Sixthly, match each segment with the generated hash sequences and save the auxiliary information for each matched segment in the image in a file. Lastly, send the stego image and the auxiliary information file to the receiver. The experimental results show that the CIS method produces high capacity compared with previous CIS methods.